EFEKTIVITAS DARK COKLAT DAN KUNYIT ASAM TERHADAP PENURUNAN DISMINORE PADA REMAJA PUTRI DI LENTENG AGUNG TAHUN 2024 - Apriyani, Magdalena Tri Putri (Jurnal Ilmu Kebidanan, 2024)
Menstrual pain (Dysmenorrhea) is caused by contractions originating from the uterine muscle. The impact of menstrual pain causes discomfort in daily physical activities. This complaint is related to repeated absences from school or work, which can disrupt productivity. Pain also affects the emotional status of feelings, irritability, depression and anxiety. Approximately 70%-90% of cases of menstrual pain occur in teenagers and early adults which will affect their academic, social and sports activities. The purpose is to determine the effectiveness of dark chocolate and turmeric on reducing dysmenorrhea in young women in Lenteng Agung. Method: quasi-experiment with non-equivalent control group design with Wilcoxon Signed Rank Test analysis. The population in the study was 30 and the sample in this research was 30 respondents, using random sampling techniques. The research instrument used was an observation sheet. Results: The results of the analysis show that there is an influence between giving dark chocolate and sour turmeric on reducing dysmenorrhea in young women. Based on the results of statistical tests, it was obtained that the ρ value was 0.05 < 0.05, so H0 was rejected and H1 was accepted. Keywords: Dark chocolate, sour turmeric, dysmenorrhea